Fibrin glue injection: Rescue treatment for refractory post‐sphincterotomy and post‐papillectomy bleedings. Issue 5 (27th November 2020) - Orlandini, Beatrice; Schepis, Tommaso; Tringali, Andrea; Familiari, Pietro; Boškoski, Ivo; Borrelli de Andreis, Federica; Perri, Vincenzo; Costamagna, Guido
Abstract : Objectives: Endoscopic sphincterotomy (ES) and papillectomy (EP) are associated with a non‐negligible risk of post‐procedural bleeding. Despite first‐line endoscopic hemostasis being achieved by several methods, patients may experience bleeding persistence or recurrence. In such cases, fibrin glue (FG) injection may be used as a rescue therapy before more invasive approaches. The aim of this study was to evaluate the efficacy and safety of endoscopic FG injection to treat refractory post‐ES and post‐EP bleeding. Methods: Data were collected retrospectively from patients with refractory immediate or delayed bleeding following ES or EP, between October 2007 and November 2019, at a single institution. Clinical success was defined as bleeding control after FG injection. Results: Overall, 70 patients were included. Clinical success was reached in 64 (91.4%) patients after one session of FG injection. Of six (8.6%) patients in whom the treatment failed, one required subsequent insertion of a fully covered self‐expanding metal stent (FC‐SEMS) due to immediate massive bleeding, while five experienced bleeding recurrence. Such events were managed with an additional session of FG injection that failed in two cases. Therefore, one patient underwent FC‐SEMS plus selective embolization, whereas the other underwent diagnostic arteriography. No severe periprocedural complications occurred. Two cases of intrabiliary glue migration were treated by endoscopic removal with a retrieval basket. Conclusions: Rescue therapy with endoscopic FG injection appears to be effective and safe to treat refractory post‐ES and post‐EP bleeding. Further studies are required to confirm these preliminary data.